Synthesis of Gold (Au) Nanoparticles by using Bioreductor of Cocoa (Theobroma cacao L.) Rind Extract and It's Antibacterial Activity Test - Sabir, Fabriani; Arif, Abdur Rahman; Kasim, Syahruddin (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2024)
Research on the Synthesis of Gold (Au) Nanoparticles by using Bioreductor of Cocoa (Theobroma cacao L.) Rind Extract and Its Antibacterial Activity Test has been done. This Green Synthesis method uses methanol as a solvent to extract organic compounds in the cocoa rind that function as bioreductants. The results of the synthesis were continued by testing its activity as an antibacterial. The form of gold nanoparticles can be confirmed after 30 minutes of stirring. The characterization of gold nanoparticles was carried out using a UV-Vis spectrophotometer, Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), and Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX). Based on the analysis of UV-Vis spectrophotometer, the maximum wavelength was at 553 nm with an absorbance value of 0.164. The FTIR results indicate the presence of a hydroxyl group that acts as a metal ion reducing agent so that it is not charged, while the results of the XRD analysis confirm that the gold nanoparticle crystals are Face Centered Cubic (FCC) and based on the Scherrer approach the particle size distribution has an average diameter of 6.303 nm. The SEM-EDX results showed that the gold nanoparticles had a spherical shape and were located in the M electron shell. The gold nanoparticles had an inhibitory zone of 8.9 mm in Pseudomonas aeruginosa and 7.6 mm in Bacillus subtilis bacteria.